Dependency and health utilities in stroke: data to inform cost-effectiveness analyses - Ali, Myzoon; MacIsaac, Rachael; Quinn, Terence J.; Bath, Philip M.W.; Veenstra, David L.; Xu, Yaping; Brady, Marian C.; Patel, Anita; Lees, Kennedy R. (SAGE Publications, 2017)
Introduction: Health utilities (HU) assign preference weights to specific health states and are required for costeffectiveness analyses. Existing HU for stroke inadequately reflect the spectrum of post-stroke disability. Using international stroke trial data, we calculated HU stratified by disability to improve precision in future cost-effectiveness analyses. Materials and methods: We used European Quality of Life Score (EQ-5D-3L) data from the Virtual International Stroke Trials Archive (VISTA) to calculate HU, stratified by modified Rankin Scale scores (mRS) at 3 months. We applied published value sets to generate HU, and validated these using ordinary least squares regression, adjusting for age and baseline National Institutes of Health Stroke Scale (NIHSS) scores. Results: We included 3858 patients with acute ischemic stroke in our analysis (mean age: 67.5+-12.5, baseline NIHSS: 12+-5). We derived HU using value sets from 13 countries and observed significant international variation in HU distributions (Wilcoxon signed-rank test p<0.0001, compared with UK values). For mRS=0, mean HU ranged from 0.88 to 0.95; for mRS=5, mean HU ranged from -0.48 to 0.22. OLS regression generated comparable HU (for mRS=0, HU ranged from 0.9 to 0.95; for mRS=5, HU ranged from -0.33 to 0.15). Patients’ mRS scores at 3 months accounted for 65–71% of variation in the generated HU. Conclusion: We have generated HU stratified by dependency level, using a common trial endpoint, and describing expected variability when applying diverse value sets to an international population. These will improve future cost-effectiveness analyses. However, care should be taken to select appropriate value sets.